Thinning of Macular Neuroretinal Layers Contributes to Sleep Disorder in Patients With Type 2 Diabetes Without Clinical Evidences of Neuropathy and Retinopathy - Ishibashi, Fukashi; Tavakoli, Mitra (Frontiers in Endocrinology, 2020)
Aims: To investigate the impact of thinning at individual grids of macular neuroretinal layers, clinical factors and inadequate light exposure on the specific components of sleep disorder in patients with type 2 diabetes. Methods: One hundred and twenty-four patients with type 2 diabetes without clinical evidence of diabetic retinopathy and neuropathy (HbA1c: 8.3%, diabetes duration; 8.7 years) and 54 age- and sex-matched control subjects (HbA1c: 5.6%) underwent detailed clinical, neurological and ophthalmological examinations. The sleep disorder was assessed by the Pittsburgh Sleep Quality Index Japanese Version (PSQI-J). The temporal structures of daily life were assessed by Munich Chronotype Questionnaire Japanese Version. The thickness at 9 grids defined by Early Treatment Diabetic Retinopathy Study of 9 macular neuroretinal layers was determined by swept-source optical coherence tomography and OCT-Explorer. The associations between the individual components of sleep disorders and the thickness at each grid of macular neuroretinal layers, clinical factors or the temporal structures of daily life were examined. Results: The prevalence of the sleep disorder, global score and 4 individual PSQI-J scores in patients with type 2 diabetes were higher than control subjects. The thickness of 2 and 5 grids of 2 inner retinal layers and 4-7grids of 4 outer retinal layers in patients with type 2 diabetes was thinner than those in control subjects. The thickness at1-8 grids of 4 outer retinal layers in type 2 diabetic patients were inversely associated with global score and 5 individual scores of sleep disorder. The thinning at 1-2 grids of the inner plexiform layer was related to 3 high individual scores of sleep disorder. The inappropriate light exposure was associated with sleep disorder and altered macular neuroretinal layers. The high HbA1c and LDL-cholesterol levels were related to the high global score and 2 individual scores of sleep disorder, respectively. Conclusion: In patients with type 2 diabetes, the thinning at grids of the inner plexiform layer and outer retinal layers were associated with the high scores of specific components of the sleep disorder. The sleep disorder was also related to hyperglycemia, dyslipidemia, and inappropriate light exposure.